2015
DOI: 10.1002/app.42430
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the foamability and mechanical properties of foamed polypropylene blends by using extensional rheology

Abstract: In this article, the influence of the rheological behavior of miscible blends of a linear and a high melt strength, branched, polypropylene (HMS PP), on the cellular structure and mechanical properties of cellular materials, with a fixed relative density, has been investigated. The rheological properties of the PP melts were investigated in steady and oscillatory shear flow and in uniaxial elongation in order to calculate the strain hardening coefficient. While the linear PP does not exhibit strain hardening, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 37 publications
2
56
0
Order By: Relevance
“…Another possible rationale behind the reinforcement detected in the cellular nanocomposites compared to the solid nanocomposites with the same sepiolite content is the improved dispersion of the particles in the cellular materials due to the foaming process. Multiple studies have demonstrated that foaming can lead to better dispersion of particles . To validate this hypothesis, the number of particle aggregates was determined before and after the foaming process for the material with 2 wt% of sepiolites (for which the highest enhancement of the modulus was observed at a relative density close to 0.5) using tomography and image analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possible rationale behind the reinforcement detected in the cellular nanocomposites compared to the solid nanocomposites with the same sepiolite content is the improved dispersion of the particles in the cellular materials due to the foaming process. Multiple studies have demonstrated that foaming can lead to better dispersion of particles . To validate this hypothesis, the number of particle aggregates was determined before and after the foaming process for the material with 2 wt% of sepiolites (for which the highest enhancement of the modulus was observed at a relative density close to 0.5) using tomography and image analysis.…”
Section: Resultsmentioning
confidence: 99%
“…These outcomes indicate that the particles are less aggregated in the cellular samples than in the solids. This effect is related to the stretching suffered by the polymer chains during the cell growth . The enhanced dispersion is expected to enhance the mechanical properties of the solid phase.…”
Section: Resultsmentioning
confidence: 99%
“…These foams are discs with a diameter of 180 mm and a height of 10 mm. A more detailed description of the ICM technique can be found elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…Moreover, composites containing three different clay contents (2.5, 5, and 7.5 wt %) were generated in order to analyze the effect of the clay content. Finally, cellular materials were produced by the Improved Compression Moulding (ICM) route in order to analyze the effect of the foaming process . ICM was selected because in this foaming process the material is only subjected to temperature and pressure and hence, there are no other forces associated to the foaming process which could contribute to the clay exfoliation (such as shear forces in extrusion foaming).…”
Section: Introductionmentioning
confidence: 99%
“…To obtain larger anisotropy ratios, processes designed specifically are required. In the work of Laguna-Gutierrez et al [30] the improve compression molding (ICM) technique was employed to produce polypropylene foams with controlled expansion ratios of the order of 5 and anisotropy ratios around 3. In the work of Arora et al [31] anisotropic polystyrene foams were produced using supercritical carbon dioxide as blowing agent.…”
Section: Introductionmentioning
confidence: 99%